2009
DOI: 10.1158/1535-7163.targ-09-b42
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B42: ATM deficiency sensitizes gastric cancer cells to the PARP inhibitior olaparib

Abstract: Ataxia telangiectasia mutated (ATM) is a protein kinase that regulates cell-cycle checkpoints, DNA repair and recombination (1). It has been shown that ATM interacts with and regulates NBS1 and BRCA complex which is essential for the homologous recombination (HR) repair in response to the DNA double-strand break (DSB) damage (2). These observations suggest that tumor cells with defective ATM expression or activity subsequently leading to HR deficiency are likely more sensitive to the targeted therapeutic/chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…ATM deficiency has been shown to sensitize lymphoid tumor cells [6,7] to the PARP inhibitor olaparib, and sensitivity to gastric cell lines was also suggested to be due to low levels of ATM expression [10]. We assessed the concordance in ATM IHC between preoperative endoscopic biopsy or metastatic tumor samples and whole tissue or primary tumor samples in two independent cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATM deficiency has been shown to sensitize lymphoid tumor cells [6,7] to the PARP inhibitor olaparib, and sensitivity to gastric cell lines was also suggested to be due to low levels of ATM expression [10]. We assessed the concordance in ATM IHC between preoperative endoscopic biopsy or metastatic tumor samples and whole tissue or primary tumor samples in two independent cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…ATM mRNA and protein levels were found to be decreased in gastric cancers compared to normal samples, phosphorylated ATM was consistently present in gastric cancers, and low levels of phosphorylated ATM were significantly correlated with poor differentiation, lymph node metastasis and poor 5-year survival [9]. Guo et al [10] observed that ATM deficiency sensitizes cells to the growth-inhibitory effects of olaparib and SN-38 (the active metabolite of irinotecan) in gastric cancer cells with reduced ATM expression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these prerogatives, data in clear favor of platinum-based treatments are contradictory in GC [85]. Preclinical models suggest an effect of poly(ADPribose) polymerase (PARP) inhibitors (PARPi) in GC cells, confirmed by the promising results of the randomized phase II trial in advanced GC designed to demonstrate the safety and efficacy of adding olaparib to taxane-based chemotherapy [82,86]. The failure of the phase III GOLD trial in advanced GC in the subgroup of ATM low patients did not lead to further development of PARPi in early stages and implied that in GC, the DDR mechanisms have a complexity that we do not yet fully understand [87].…”
Section: Other Targeted-therapiesmentioning
confidence: 99%
“…Low expression of ATM in GC is associated with poorlydifferentiated histology, lymph node involvement, and worse overall 5-year survival among patients undergoing curative surgical resection (11). Pre-clinical models have suggested increased sensitivity of ATM deficient cells to inhibition with olaparib and SN-38 though platinum associations remain understudied (12). Recently, the phase III GOLD trial failed to show a survival benefit for olaparib in unselected advanced GC progressing after first-line therapy.…”
Section: Introductionmentioning
confidence: 99%